Online Business Ethics Violations: The Unspoken Danger Behind Medan‎ City' Digital Screens - Ahmad Kholil; Azhari Akmal Tarigan; Muhammad Syukri Albani Nasution (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The phenomenon of online business in Medan City is growing rapidly, but it is accompanied by various‎ violations of business ethics that harm consumers and reduce public trust. ‎This research aims to analyze the forms of online business ethics violations, the factors‎ causing them, and their impact on the digital trade ecosystem. Using a qualitative‎ approach through case studies, data was collected from in-depth interviews with business‎ actors, consumers, and sharia economic experts. The results identified various‎ forms of violations such as price manipulation, data misuse, and fraudulent practices. ‎The main factors that trigger violations include weak regulations, low digital literacy,‎ and unfair business competition. The resulting impacts include a decline in‎ consumer confidence and a slowdown in the development of the digital economy. The novelty of this‎ research lies in the integration of the perspectives of business actors, consumers, and sharia economic experts in‎ understanding the dynamics of online business ethics violations in Medan City.‎